A qualitative evidence synthesis of patient perspectives on migraine treatment features and outcomes. Issue 2 (5th January 2023) - Urtecho, Meritxell; Wagner, Brittin; Wang, Zhen; VanderPluym, Juliana H.; Halker Singh, Rashmi B.; Noyes, Jane; Butler, Mary E.; Murad, Mohammad Hassan
Abstract: Objectives: We aimed to identify migraine treatment features preferred by patients and treatment outcomes most valued by patients. Background: The values and preferences of people living with migraine are critical for both the choice of acute therapy and management approach of migraine. Methods: We conducted a qualitative evidence synthesis. Two reviewers independently selected studies, appraised methodological quality, and undertook a framework synthesis. We developed summary of findings tables following the approach of Grading of Recommendations, Assessment, Development and Evaluations Confidence in the Evidence from Reviews of Qualitative Research to assess confidence in the findings. Results: Of 1691 candidate references, we included 19 studies (21 publications) involving 459 patients. The studies mostly recruited White women from North America (11 studies) and Europe (8 studies). We identified eight themes encompassing features preferred by patients in a migraine treatment process. Themes described a treatment process that included shared decision‐making, a tailored approach, trust in health‐care professionals, sharing of knowledge and diversity of treatment options, a holistic approach that does not just address the headache, ease of communication especially for complex treatments, a non‐undermining approach, and reciprocity with mutual respect between patient and provider. In terms of the treatment itself, seven themes emerged including patients' preferences for nonpharmacologic treatment, high effectiveness, rapidity of action, long‐lasting effect, lower cost and more accessibility, self‐management/self‐delivery option that increases autonomy, and a mixed preference for abortive versus prophylactic treatments. The treatment outcomes that have high value to patients included maintaining or improving function; avoiding side effects, potential for addiction to medications, and pain reoccurrence; and avoiding non‐headache symptoms such as nausea, vomiting, and sensitivity to light or sounds. Conclusion: Patient values and preferences were individually constructed, varied widely, and could be at odds with conventional medical perspectives and evidence of treatment effects. Considering the availability of numerous treatments for acute migraine, it is necessary that decision‐making incorporates patient values and preferences identified in qualitative research. The findings of this qualitative synthesis can be used to facilitate an individually tailored approach, strengthen the patient–health‐care system relationship, and guide choices and decisions in the context of a clinical encounter or a clinical practice guideline.